Customs revenue in Ghana: Recent trends and their causes - Edward Abrokwah; Ebenezer Bob-Eshun; Harriet Conron; Abdul Malik Iddrisu; Daniel Nuer; Ross Warwick (Institute for Fiscal Studies (IFS), 2021)
The collection of tax revenue at customs has long been an important revenue source in Ghana. However, recent years have seen substantial falls in customs revenue collections, with the share of taxes collected at the country's ports falling from 42% in 2017 to 30% in 2019. With increasing tax revenues high on the government's agenda, understanding the underlying drivers of such trends is important for public policy. To that end, this report analyses Ghana's customs revenues in historical and international context, before using detailed data to investigate the drivers of revenue in recent years.
Keywords: 330; Steuereinnahmen; Import; Importbeschränkung; Zollpolitik; Ghana